Clinical and arthroscopic findings in recreationally active patients - Fowler Elizabeth M; Horsley Ian G; Rolf Christer G (BMC, 2010)
Abstract Objective To examine the diagnostic accuracy of standard clinical tests for the shoulder in recreational athletes with activity related pain. Design Cohort study with index test of clinical examination and reference standard of arthroscopy. Setting Sports Medicine clinic in Sheffield, U.K. Participants 101 recreational athletes (82 male, 19 female; mean age 40.8 ± 14.6 years) over a six year period. Interventions Bilateral evaluation of movements of the shoulder followed by standardized shoulder tests, formulation of clinical diagnosis and shoulder arthroscopy conducted by the same surgeon. Main Outcome Measurements Sensitivity, specificity, likelihood ratio for a positive test and over-all accuracy of clinical examination was examined retrospectively and compared with arthroscopy. Results Isolated pathology was rare, most patients (72%) having more than one injury recorded. O'Brien's clinical test had a mediocre sensitivity (64%) and over-all accuracy (54%) for diagnosing SLAP lesions. Hawkins test and Jobe's test had the highest but still not impressive over-all accuracy (67%) and sensitivity (67%) for rotator cuff pathology respectively. External and internal impingement tests showed similar levels of accuracy. When a positive test was observed in one of a combination of shoulder tests used for diagnosing SLAP lesions or rotator cuff disease, sensitivity increased substantially whilst specificity decreased. Conclusions The diagnostic accuracy of isolated standard shoulder tests in recreational athletes was over-all very poor, potentially due to the majority of athletes (71%) having concomitant shoulder injuries. Most likely, this means that many of these injuries are missed in general practice and treatment is therefore delayed. Clinical examination of the shoulder should involve a combination of clinical tests in order to identify likely intra articular pathology which may warrant referral to specialist for surgery.